Ant fauna of Walnut orchards of the Shahrekord and Saman counties (Chaharmahal & Bakhtiari Province) with the report of some ant species as symbiont of Walnut aphids - Arsalan Khalili-Moghadam; Zarir Saeidi (نامه انجمن حشره‌شناسی ایران, 2023)
Walnut (Juglans regia L.) is known as one of the most important dried fruits of the world. Chaharmahal & Bakhtiari Province, with approximately 7400 hectares, is one of the most important cultivation areas in Iran. Considering the rich fauna of ants in walnut orchards and their relation with walnut pests (such as Leopard Moth and aphids), this study was conducted in Shahrekord and Saman orchards during 2021-2022. Totally, 13 species belonging to 10 genera and three subfamilies, were collected and identified. Among them, Messor muticus (Nylander, 1849) and Tetramorium indocile Santschi, 1927 belonging to the subfamily Myrmicinae are reported for the first time from Iran, and Chaharmahal & Bakhtiari Province, respectively. Furthermore, this study revealed that Tapinoma karavaievi Emery, 1925, Lasius neglectus Van Loon, Boomsma & Andrasfalvy, 1990, and Crematogaster subdentata Mayr, 1877 have symbiotic relationships with walnut aphids and lecanium scales and are probably effective in the distribution and damage of these pests.